Syu'aib a.s dalam Perspektif Al-Qur'an - Muhammad Thaib Muhammad (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Syu'aib a.s is one of the prophets mentioned ten times in several surahs in the Al-Qur'an al -Karim. His full name is Syu'aib bin Maikiil bin Masyjur ibn Madyan, the son of Prophet Ibrahim a.s and his mother was the son of Prophet Lut a.s. He was sent to Ahlu Madyan who had deviated from the religion of Abraham a.s. Ahlu Madyan lives in a fertile area near the bay of Aqabah. Ahlu Madyan cheated on the scales and did damage to the face of the earth. When Syu'aib a.s delivered his message inviting Ahlu Madyan to return to the true religion, they refused the invitation with great arrogance and humiliation. Even asked Syu'aib to bring something down from the sky and asked Syu'aib a.s to stop preaching. If it doesn't stop they will take it out with the believers from their village. As a result of Ahlu Madyan's denial and arrogance, Allah lowered the heat for seven days, then brought a black cloud so that they took shelter under it. Ahlu Madyan thought it would rain. But Allah sent down a rain of fire and a strong wind so that all of them died lying in their homes. That is how Allah SWT destroyed Ahlu Madyan.AbstrakSyu’aib a.s adalah salah seorang nabi yang yang disebut dalam Al-Qur’an al –Karim sebanyak sepuluh kali dalam beberapa surat. Nama lengkapnya Syu’aib bin Maikiil bin Masyjur ibnu Madyan Anak Nabi Ibrahim a.s dan Ibunya adalah anak Nabi Luth a.s. Beliau diutus kepada ahlu Madyan yang sudah menyimpang dari agama Ibrahim a.s. Ahlu Madyan tinggal di sebuah wilayah yang subur dekat teluk Aqabah. Ahlu Madyan melakukan kecurangan dalam timbangan dan melakukan kerusakan di muka bumi. Ketika Syu’aib a.s menyampaikan dakwah mengajak Ahlu Madyan kembali kepada agama yang benar, mereka menolak ajakan tersebut dengan penuh kesombongan dan penghinaan. Bahkan meminta Syu’aib untuk menurunkan sesuatu dari langit serta meminta Syu’aib a.s untuk berhenti berdakwah. Jika tidak berhenti mereka akan mengeluarkannya bersama orang beriman dari desa mereka. Akibat dari keingkaran dan kesombongan Ahlu Madyan tersebut, Allah menurunkan kepanasan selama tujuh hari, kemudian mendatangkan awan hitam sehingga mereka berteduh dibawahnya. Ahlu Madyan menyangka hujan akan turun. Akan tetapi Allah menurunkan hujan api dan angin kencang , sehingga semua mereka mati bergelimpangan di rumah mereka masing-masing. Begitulah Allah SWT menghancurkan Ahlu Madyan